The Ethical Development of Boys in Jean-Jacques Rousseau’s Emile and Jean-Baptiste Greuze’s Artworks - Lerner, Loren (Lumen, 2021)
This article considers the ways in which a series of artworks by French artist Jean-Baptiste Greuze focus on the father’s ethical education of his male children, reading these as a close visualization of the pedagogical theories of Rousseau. Through paintings that contemplate family life, religious sentiment, filial piety, obedience versus disobedience, illness, and death, Greuze’s images of male youth coalesce with the ethics promoted in Rousseau’s novel Emile—stressing in particular the compassion and good conscience that a boy should develop under the guidance of his father to become a man of virtue. In so doing, the artist responds to some of the key historic issues and social beliefs affecting male youth during his era: the necessity of apprenticed boys to leave home; an idealization of country living and farming as the best occupation for the adult male; and an overwhelming concern, widespread during this heightened period of warfare and unrest preceding the French Revolution, that young men go astray when they become soldiers.